New horizon in phospha-michael reaction: Ultrafast double addition of P-H bond-bearing nucleophiles to alectron-deficient triple bonds and its use for functional monomer synthesis and polymer modification - ÇAKMAKÇI, EMRAH; FINDIK, VOLKAN; ERDEM, SAFİYE (My University, 2023)
In this work, a novel, straightforward, robust, fast, and organocatalyst-mediated phospha-Michael reaction (OCPMR) was developed for the addition of phosphorus nucleophiles to electron-deficient alkynes. Several P-H bond-bearing compounds with either fully aliphatic or aromatic units were utilized for this newly developed reaction, and it was found that phosphorous species containing only aromatic groups reacted with activated alkynes within 5 min at room temperature. The reaction led to a fast double-addition of the phosphorous compounds to the triple bond of the alkynes. An in-depth analysis of the reaction mechanism and selectivity of this OCPMR was performed using computational methods. Using the developed method, double-phosphorylated allyl-functional monomers were synthesized and subsequently used for the synthesis of linear and crosslinked polymers via thiol-ene photopolymerization. The thermoset materials exhibited LOI values as high as 26.4%. We also showed that polyesters having electron-deficient triple bonds could be easily functionalized with the P-H bond-bearing compounds. The synthetic method proposed herein promises easy and fast P-C bond formation under mild reaction conditions, and it is a straightforward method for the synthesis of phosphorus-containing monomers, linear or crosslinked polymers, and for polymer post-functionalization. We believe this feature will be of great interest not only to material chemists and polymer scientists but also to organic chemists, pharmaceutical researchers, etc.
Keywords: Kimya; Biyokimya; Biyoinorganik Kimya; Fizikokimya; Polimer Karakterizasyonu; İnorganik Kimya; Temel Bilimler; Mühendislik ve Teknoloji; Chemistry; Biochemistry; Bioinorganic Chemistry; Physical Chemistry; Characterization of Polymers; Inorganic Chemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Malzeme Bilimi; KİMYA, İNORGANİK VE NÜKLEER; POLİMER BİLİMİ; KİMYA, ORGANİK; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); MATERIALS SCIENCE; CHEMISTRY; CHEMISTRY, INORGANIC & NUCLEAR; POLYMER SCIENCE; CHEMISTRY, ORGANIC; MATERIALS SCIENCE, MULTIDISCIPLINARY; Organik Kimya; Fizik Bilimleri; Polimerler ve Plastikler; İnorganik kimya; Malzeme Kimyası; Organic Chemistry; Physical Sciences; Polymers and Plastics; Materials Chemistry